Interaction parameters of oxygen and deoxidants in liquid iron (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
During decades before the evolution of more powerful computational tools, simplified formalisms such as the Wagner dilute solution formalism, have been successfully used in the study of deoxidation reactions of steel.  This formalism rely on the introduction of interaction coefficients to account from deviations from Henry’s Law caused either by deviation from very dilute solutions or by the effect of interaction between solutes.  With the evolution of thermodynamic modeling and of the CALPHAD method, the fact that thermodynamic descriptions using these parameters were envisaged only to be used at relatively dilute solution has been sometimes overlooked and the formalism has been criticized for deviating from reality in non-dilute solutions.  In this work we show that the interaction parameters used in this formalism bear significant correlation with properties that have physical meaning, related to the solutes and to the solvent.  We focus on the interactions in systems Fe-M-O, where M is a deoxidant, and demonstrate the correlation of the interaction coefficients with heats of formation of the corresponding oxides and revisit their correlation with the atomic number of the deoxidants.  Finally, we show that this not only help support the physicochemical soundness of the formalism but also provides an useful way of checking the consistency of data presented in this formalism.